Efeito da utilização de norfloxacina em infecções urinárias no desenvolvimento de candidíase vulvovaginal (CVV) - Rocha, Rodrigo Manieri (2014)
Vulvovaginal candidiasis (VVC) is an extremely important pathology in the clinical practice. Some studies revealed that antibiotics can interfere in VVC incidence. The present study evaluated the effect of norfloxacin to treat uncomplicated urinary infections on the incidence of VVC. Microbiological methods were performed to identify the presence of yeast infections. 77 patients (30 patients in the case group and 47 patients in the control group) were enrolled in the study. Were performed Pap smear, bacterioscopy and yeast culture in the patient first visit and 4 weeks after. Were found 2 positive samples of candidiasis, (1 prior and 1 after treatment) and 11 positive samples in the control group (4 in the first sample and 7 in the second sample).The results shows that the use of antibiotic did not changed the yeast detection rates, with Odds Ratio (OR) in the case group of 0.19 (CI 0.02 - 1.63, p 0,13), relative to the control group. The use of norfloxacin does not increase the VVC incidence. This information shows that the use of specific antibiotics do not increase vaginal yeast infections and another studies must be performed individualizing antibiotics and infection sites, to correctly define witch situations can increase VVC incidence.